Teachers' Ability in Identifying Children with Low Academic Achievements in Inclusive Education - Damastuti, Eviani; Rapisa, Dewi Ratih (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2021)
Children with low academic achievement are one of the problems that are often found in schools but, in general, children with this condition often cannot be identified by teachers. Whereas the success of educational services for children with low academic achievement is determined by the ability of teachers to identify children. Therefore, the purpose of this study was to determine the teacher's ability to identify children with low academic achievement in schools providing inclusive education. This quantitative descriptive research was conducted at 4 elementary schools in Banjarmasin City and Banjar Regency with the number of research subjects on 28 classroom teachers. Data collection was carried out using questionnaires and interviews and then analyzed quantitatively descriptively. The results showed that the teacher's ability to identify children with low academic achievement with an average of 33.33% both in screening, referral, and classification functions. At the stage of screening, the process carried out is still incomplete, because identification is carried out only using identification instruments, simple tests, and inadequate supporting documents (Family Cards (KK), birth certificates, children's data). Most of the teachers have not observed children's abilities, interviewed , and completed IQ test results. At the referral stage, the teacher has not collaborated with professional staff. Most students with low academic achievement are classified by teachers as slow learners, without knowing their IQ scores. The teachers with lack of ability to understand the process of identifying children with special needs will determine the handling of children with special needs in schools providing inclusive education.